PERAN LEMBAGA PENDIDIKAN TAHFIZ DALAM MENINGKATKAN PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH DASAR DILEMBAGA PENDIDIKAN TAHFIZ QUR’AN MUAMALAH DESA SEMPADIAN KECAMATAN TEKARANG TAHUN 2021-2022 - Saparti Aisyah; Suhari; M. Sabiqul Huda (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
In general, people think that LPTQ only teaches how to read the Qur'an, but actually LPTQ also provides Islamic education learning. In addition, the lack of Islamic religious education learning in public schools makes students have to get additional Islamic religious education learning. The majority of Islamic religious education learning in public schools is only one meeting a week so it is very unlikely that students will be able to understand more about Islamic religious education learning. The research focus in this study are: 1) How is the Role of Tahfiz Education Institution in Improving Islamic Religious Education at Muamalah Qur'an Tahfiz Education Institution, Sempadian Village, Tekarang District in 2021-2022? 2) What are the supporting and inhibiting factors at the Muamlah Qur'an Tahfiz Education Institute (LPTQ) Sempadian Village, Tekarang District 2021-2022? The research approach used by researchers is a qualitative approach. The purpose of research with this qualitative approach is to produce descriptive data in the form of written or spoken words from people who can be observed. This type of research is field research, which is research conducted by collecting data and information directly in the field (research area). Based on the results of the study found that: First, LPTQ Muamlah, shows that there are several PAI materials taught in LPTQ Muamlah. Some of these materials include reading the Qur'an, faith, worship, morals, fiqh and Islamic history. Based on the six learning materials, it shows that LPTQ Muamalah teaches about PAI materials. Second, the supporting and inhibiting factors in improving PAI learning in LPTQ have supporting and inhibiting factors. It can be seen from several supporting and inhibiting factors. So it is clear that in LPTQ Muamalah the role of tahfiz educational institutions has supporting and inhibiting factors.